Evaluación del consumo del portador de energía eléctrica en el edificio central del Instituto Tecnológico Superior Aeronáutico de la ciudad de Latacunga en el período 2009-2013, para conseguir ahorro energético. Diseño de un sistema de gestión energética. - Guerrero Rodríguez, Lucía Eliana (2015)
Light sheets must pay monthly for the electricity consumption, shows the insufficient level of energy management in the Superior Aeronautical Institute of Technology, under it, which arises, is to implement a management system for energy efficiency in the central building of the ITSA, based on field research, bibliographic and documentary, which helped to develop an energy assessment and a proposal to help reduce consumption levels of the carriers to avoid irrational waste of energy mainly lighting systems, where it has the biggest waste of potential, lack of control. Changing the lighting system, for a more efficient one as proposed in this paper, would be improved by 71%, power consumption, since it reduces of 216.478 kWh a 142.860 kWh annually. In Costs, of $10.823,90 would be paid $7132,75, that is to say, it saves $3.691 a year, which could be used in the implementation of laboratory equipment.